Perturbation profile of elite football - a cross-sectional analysis of the goals and goal scoring opportunities immediately before and after goal scoring of the 1st German Bundesliga - Fischer, J.; Fischer, D.; Keiner, M. (International Journal of Performance Analysis in Sport, 2022)
The sport of football cannot be represented holistically with a quantitative approach. The basis for this analysis was the construct of dynamic system theory. Based on the method of systematic game observation, a perturbation (= triggers that transfer a system into a state of instability) sign system was made, distinguishing between offensive (oP) and defensive perturbations (dP). The subject of the study was goal critical situations five minutes before and after goal scoring. The present study is a partial survey of the 1st Bundesliga season 2019/20, insofar as game Days 1.-17. (n = 153 games) were evaluated by video according to two independent raters. The average number of perturbations required to score a goal was 1.69 perturbations (on average 1.52 oP & 0.17 dP), while an average of 1.30 perturbations (on average 1.15 oP & 0.15 dP) was sufficient to create a goal scoring opportunity. The group technical tactical offensive perturbation low pass revealed the largest proportion of all perturbations, at 28%. Therefore, a game plan should be designed to create superior numbers close to the ball to avoid the loss of stability.